2019
DOI: 10.1063/1.5089683
|View full text |Cite|
|
Sign up to set email alerts
|

An experimental study on the effect of swirl number on pollutant formation in propane bluff-body stabilized swirl diffusion flames

Abstract: The combustion characteristics of propane/air bluff-body stabilized swirl diffusion flames within the turbulent regime are studied experimentally to determine the effect of the swirl number on the flame dynamics and pollutant emissions. The investigated burner consists of a central bluff body with an annulus to introduce the tangential and axial air flows. Results show that in low annulus Reynolds numbers (ReS), the temperature distribution is more affected by the overall equivalence ratio (φo), which is calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The injection flow rate of the gaseous phase is kept constant, fixing a bulk Reynolds number, R e 0 = 2 U b u l k R / ν = 6000, that corresponds to a configuration of technological interest as concerns swirl-stabilized combustors. 46,47 A nearly-saturated condition is prescribed for the air-acetone vapor mixture at the inflow section, i.e., S * = Y v / Y v , s = 0.99, where S * is the saturation, Y v is the actual vapor mass fraction on the inflow section and Y v , s false( p 0 , T 0 false) is the vapor mass fraction in fully-saturated condition, evaluated at the inflow temperature and pressure. The acetone-to-air mass flow rate ratio is set to normalΨ = m ˙ a c t / m ˙ a i r = 0.28, with m ˙ a c t = m ˙ a c t , l + m ˙ a c t , v being the sum of liquid and gaseous acetone mass flow rates.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The injection flow rate of the gaseous phase is kept constant, fixing a bulk Reynolds number, R e 0 = 2 U b u l k R / ν = 6000, that corresponds to a configuration of technological interest as concerns swirl-stabilized combustors. 46,47 A nearly-saturated condition is prescribed for the air-acetone vapor mixture at the inflow section, i.e., S * = Y v / Y v , s = 0.99, where S * is the saturation, Y v is the actual vapor mass fraction on the inflow section and Y v , s false( p 0 , T 0 false) is the vapor mass fraction in fully-saturated condition, evaluated at the inflow temperature and pressure. The acetone-to-air mass flow rate ratio is set to normalΨ = m ˙ a c t / m ˙ a i r = 0.28, with m ˙ a c t = m ˙ a c t , l + m ˙ a c t , v being the sum of liquid and gaseous acetone mass flow rates.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Research studies have presented several important parameters that influence combustion instability characteristics in gas turbines: the swirl number, equivalence ratio, combustion design, and fuel compositions. Jalalatian et al [23] have performed experiments on the effect of the swirl number, equivalence ratio, and Reynolds numbers on diffusion flame structure and pollutant emissions. They demonstrated that when the overall equivalence ratio (the global equivalence ratio) increases, the flame length enhances, increase in swirl number leads to a slight decrease in temperature, CO concentrations, and NO thermal concentrations.…”
Section: Introductionmentioning
confidence: 99%